Morrey Spaces are Embedded Between Weak Morrey Spaces and Stummel Classes - Nicky Tumalun; Hendra Gunawan (IndoMS, 2019)
In this paper, we show that the Morrey spaces L^1,( λp -np + n ) ( R^n ) are embedded betweenweak Morrey spaces wL^p,λ( R^n ) and Stummelclasses S_α( R^n ) under some conditions on p, λ and α . More precisely, we prove that wL^p,λ(R^n ) L^1,( λp - np + n) ( R^n ) S_α( R^n) where 1<p<∞, 0<λ<n and n-λp<α<n .We also show that these inclusion relations under the above conditions are proper.Lastly, we present an inequality of Adams' type A